Indonesia's Space Trajectory: Indonesia's Position in the Global Space Business Phase - Shinta Rahma Diana; Chandra Wijaya; Fibria Indriati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Global space is growing massively, and the current business phase has opened space for non-space actors to play a role. The government-driven space economy is shifting to commercial and new space in the initial phase. This research will examine the trajectory of Space in Indonesia and its position in the global space business phase. The research method uses a qualitative method. The study results show the trajectory of Indonesian Space, from its institutions to policies that support the growth of commercial space and new space phases. The dominance of the Government is still seen in space activities, which are mostly funded by public funds, with products resulting from the mastery of technology not yet entering the operational order. However, economic value can be generated by continuing commercial activities in the commercial space phase, namely the commercial use of space technology with data into value-added information and financial activities from the rental and import of space products by the Private Sector. Indonesia's position in the global space business phase is in the government-driven space economy, which involves several activities from commercial space.